2020
DOI: 10.1210/clinem/dgaa800
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Neuroendocrine Tumors of the Lung in MEN1: Results From the Dutch MEN1 Study Group

Abstract: Introduction Multiple Endocrine Neoplasia type 1 (MEN1)-related neuroendocrine tumors (NETs) of the lung are mostly indolent with a good prognosis. Nevertheless, cases of aggressive lung NET do occur, and therefore the management of individual patients is challenging. Aim To assess tumor growth and survival of patients with MEN1-related lung NETs at long-term follow-up. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Current MEN1 guidelines suggest imaging for BP and thymic NETs every 1 to 2 years with CT or MRI but acknowledges the uncertainty of this approach (ie, weak recommendation, very low-quality evidence) [ 1 ]. Recent studies report radiologic evidence of BP NETs in approximately 25% of MEN1 patients, but that such tumors are typically associated with low growth rates and an excellent overall survival with little excess mortality [ 3 , 4 , 9 ]. Although occasional tumors display a more aggressive disease course, the current evidence calls into question the value of frequent screening in asymptomatic patients, particularly because there is little evidence to support intervention for small, stable lesions.…”
Section: Multiple Endocrine Neoplasia Type 1 Screening: Areas Of Controversymentioning
confidence: 99%
“…Current MEN1 guidelines suggest imaging for BP and thymic NETs every 1 to 2 years with CT or MRI but acknowledges the uncertainty of this approach (ie, weak recommendation, very low-quality evidence) [ 1 ]. Recent studies report radiologic evidence of BP NETs in approximately 25% of MEN1 patients, but that such tumors are typically associated with low growth rates and an excellent overall survival with little excess mortality [ 3 , 4 , 9 ]. Although occasional tumors display a more aggressive disease course, the current evidence calls into question the value of frequent screening in asymptomatic patients, particularly because there is little evidence to support intervention for small, stable lesions.…”
Section: Multiple Endocrine Neoplasia Type 1 Screening: Areas Of Controversymentioning
confidence: 99%
“…8 Next to other manifestations as gastricand thymic NET, adrenal tumors and breast cancer, patients are also at risk of developing bpNET with a prevalence of 4.7% to 6.6% of MEN1 patients. [9][10][11][12][13][14] Clinical practice guidelines advise frequent thoracic imaging to detect and monitor these tumors. However, more recent studies have shown that MEN1-associated bpNET seem to have an indolent behavior and do not decrease overall survival in MEN1 patients, although a few aggressive cases with fatal outcome have been described.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Until now, bpNET of any type are considered the same disease, which is also reflected in the recently updated international guidelines. 25,26 However, on the basis of clinical experience and earlier reports on the natural course of sp-bpNET, MEN1-related bpNET and DIPNECH-related bpNET, the question arises whether these subtypes are in fact different entities; MEN1and DIPNECH-related bpNET rarely metastasize or lead to bpNET-related death, [9][10][11][12][13][19][20][21][22][23][24] while the prognosis of sp-bpNET seems more heterogeneousand perhaps worse than nonsporadic forms of bpNET. [3][4][5][6][7] To our knowledge, head-to-head comparisons between sp-bpNET, MEN1-related bpNET and DIPNECHrelated bpNET are lacking to date.…”
Section: Introductionmentioning
confidence: 99%
“…No scholars have suggested that MEN1-related primary tumors might occur in the liver. Although liver metastasis may occur in MEN1-related duodenopancreatic tumors [ 14 ] and thymic tumors [ 15 ], metachronous liver metastasis has been reported in only MEN1-related lung tumors [ 16 ]. No liver metastasis has been reported in the pituitary tumor or parathyroid tumor.…”
Section: Discussionmentioning
confidence: 99%